Combining low-carbon economic development and oil exploration in Brazil? An energy–economy assessment. (26th November 2018) - Lefèvre, Julien; Wills, William; Hourcade, Jean-Charles
ABSTRACT: Brazil's nationally determined contribution (NDC) pledged under the Paris Agreement has marked a new stage in its climate policy towards strengthening low-carbon economic development beyond the recent drastic cuts in emissions from deforestation. Brazil especially means to limit oil consumption driven by future economic growth and to increase energy efficiency and biofuel use in the transport sector. On the other hand, Brazil still aspires to become a major petroleum province given its huge reserves of 'pre-salt' oil. This article aims to clarify under what conditions low-carbon economic development and oil exploration can possibly be combined in Brazil and what would be the energy system, environmental and macroeconomic implications of enabling policies for doing so. To address these questions, an energy–economy computable general equilibrium (CGE) model of the Brazilian economy is used to simulate alternative scenarios up to 2030. The results first show that implementing the most recent energy plans, which take into account the new economic reality in Brazil, should lead to over 20% lower domestic CO2 emissions in 2030 than the indicative NDC target, and to the export of the bulk of newfound crude oil. Second, with the same level of oil production, deeper domestic decarbonization, triggered by additional carbon pricing and sustainable efficiency measures, appears achievable with very small gross domestic product (GDP) loss and maximum oil exports, while being aligned with a 2°C emission pathway. However, (i) extra oil exports may induce net additional emissions outside Brazil and be seen as a perverse incentive and (ii) the economic growth strategy based on high oil exports may hinder the necessary diversification of the Brazilian economy. Key policy insights Low-carbon development goals will strongly interact with oil policy in Brazil. The 2030 NDC target should be easy to achieve considering the new economic reality in Brazil. Deeper domestic decarbonization is achievable with very limited GDP loss and significant oil exports, while being aligned with a 2°C emission pathway. A broad strategic vision is needed to reconcile climate policy, energy policy and other economic development objectives.